2018
DOI: 10.1242/dev.161646
|View full text |Cite
|
Sign up to set email alerts
|

Getting leaves into shape: a molecular, cellular, environmental and evolutionary view

Abstract: Leaves arise from groups of undifferentiated cells as small primordia that go through overlapping phases of morphogenesis, growth and differentiation. These phases are genetically controlled and modulated by environmental cues to generate a stereotyped, yet plastic, mature organ. Over the past couple of decades, studies have revealed that hormonal signals, transcription factors and miRNAs play major roles during leaf development, and more recent findings have highlighted the contribution of mechanical signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 182 publications
(229 reference statements)
0
48
0
Order By: Relevance
“…On the other hand, and in support of the adaptation argument, it has also been demonstrated that leaf-blade dissection may be under oligogenic control (Sicard & al. 2014;Maugarny-Calès & Laufs 2018). This may explain our present observation that variation in ecologically adaptive and taxonomically decisive morphological features is not paralleled by genetic patterns based on molecular markers scattered throughout the whole genome like AFLP fingerprint loci.…”
Section: Genetic Differentiation Of Leucanthemum Corsicum -mentioning
confidence: 77%
“…On the other hand, and in support of the adaptation argument, it has also been demonstrated that leaf-blade dissection may be under oligogenic control (Sicard & al. 2014;Maugarny-Calès & Laufs 2018). This may explain our present observation that variation in ecologically adaptive and taxonomically decisive morphological features is not paralleled by genetic patterns based on molecular markers scattered throughout the whole genome like AFLP fingerprint loci.…”
Section: Genetic Differentiation Of Leucanthemum Corsicum -mentioning
confidence: 77%
“…Plant leaves provide a powerful model in which to explore such questions on the mechanistic basis of evolutionary change because they show substantial, heritable morphological variation at different evolutionary scales and are ecophysiologically important because they fix CO 2 in terrestrial ecosystems [16,17]. Considerable insights into the genetic basis for diversification of leaf shape have come from comparative studies of simple leaves of the reference plant A. thaliana versus complex leaves of its relative Cardamine hirsuta, where leaves are divided into distinct units called leaflets.…”
Section: Resultsmentioning
confidence: 99%
“…This shift correlates with the role of sugar in promoting the Target of Rapamycin (TOR) pathway and repressing the Sucrose-non-fermenting1-related kinase 1 (SnRK1): TOR and T6P induce cell expansion by promoting macromolecular synthesis, whereas SnRK1 promotes catabolism ( Tsai and Gazzarrini, 2014 ; Sablowski, 2016 ). Two microRNAs play opposite roles in this cellular shift: miR319 represses the expression of class II TCP factors, which are inhibitors of cell proliferation, whereas miR396 restricts the expression of GROWTH REGULATING FACTORS (GRFs), which delay differentiation ( Das Gupta and Nath, 2015 ; Maugarny-Calés and Laufs, 2018 ). The transition from an indeterminate shoot apical meristem to a determinate floral meristem also involves temporal regulation of the cellular identity.…”
Section: Mechanisms Driving Changes In Developmental Timing In Plantsmentioning
confidence: 99%